Coarctation of the aorta in Noonan‐like syndrome with loose anagen hair. Issue 5 (23rd January 2014) - Zmolikova, Michaela; Puchmajerova, Alena; Hecht, Petr; Lebl, Jan; Trkova, Marie; Krepelova, Anna
<x xml:space="preserve">Abstract</x> Noonan‐like syndrome with loose anagen hair (NS/LAH; OMIM 607721) due to a missense mutation c.4A>G in SHOC2 predicting p.Ser2Gly has been described recently. This condition is characterized by facial features similar to Noonan syndrome, reduced growth, cardiac defects, and typical abnormal hair. We report on a patient with molecularly confirmed NS/LAH with coarctation of the aorta. The girl was precipitously born at 37 weeks of gestation at home and required a 3‐min resuscitation. Increased nuchal translucency and aortic coarctation with a small ventricular septal defect were described prenatally, hypertrophic cardiomyopathy was detected postnatally. The patient presented with facial dysmorphism typical of NS with redundant skin over the nape and on the back. Short stature, relative macrocephaly, failure‐to‐thrive together with dystrophic appearance, developmental delay mainly in motor milestones and very thin, sparse, slow‐growing hair occurred a few weeks after birth. Endocrine evaluation revealed low IGF‐1 levels and borderline growth hormone deficiency. Growth hormone therapy started at 16 months had a partial effect and prevented further growth deterioration. Coarctation of the aorta is not a typical heart defect among individuals with NS/LAH, therefore our observation extends the phenotypic spectrum of this disorder. © 2014 Wiley Periodicals, Inc.